Autorretrato como construção da identidade: uma ação educativa em artes visuais para o ensino fundamental - Amaral, Viviani Patrícia Pimenta (2018)
This study focuses on identity in interface with student training through a pedagogical proposal for art teaching developed in 2016 in public urban school of Uberlândia city (MG). The research aimed to broaden student and teacher self-knowledge by highlighting identity concept in schooling environment. To stimulate student’s search for his/her identity, self-knowledge and personal construction, the drawing of portraits in classroom was thought, structured and proposed. The student self-image would be the starting point of the expression of memories, dreams, feelings and sensations. Such content had to permeate student’s artistic productions, as they reveal the personal image and link the individual with the present world pervaded by individuality and collectivity, emotion and cognition. The research relied on phenomenology as the methodology that allows understanding everyday life experiences to see reality in a dialogue with research-action in a qualitative approach. Students lived, realized and felt their experiences. They become a fundamental element of the research.